Neural mechanisms for learning self and other ownership - Patricia L. Lockwood (Nature Portfolio, 2018)
The sense of ownership – of which objects belong to us and which to others - is an important part of our lives, but how the brain keeps track of ownership is poorly understood. Here, the authors show that specific brain areas are involved in ownership acquisition for the self, friends, and strangers.